-5(6y-6)-y=-2(y-3)

Simple and best practice solution for -5(6y-6)-y=-2(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(6y-6)-y=-2(y-3) equation:


Simplifying
-5(6y + -6) + -1y = -2(y + -3)

Reorder the terms:
-5(-6 + 6y) + -1y = -2(y + -3)
(-6 * -5 + 6y * -5) + -1y = -2(y + -3)
(30 + -30y) + -1y = -2(y + -3)

Combine like terms: -30y + -1y = -31y
30 + -31y = -2(y + -3)

Reorder the terms:
30 + -31y = -2(-3 + y)
30 + -31y = (-3 * -2 + y * -2)
30 + -31y = (6 + -2y)

Solving
30 + -31y = 6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
30 + -31y + 2y = 6 + -2y + 2y

Combine like terms: -31y + 2y = -29y
30 + -29y = 6 + -2y + 2y

Combine like terms: -2y + 2y = 0
30 + -29y = 6 + 0
30 + -29y = 6

Add '-30' to each side of the equation.
30 + -30 + -29y = 6 + -30

Combine like terms: 30 + -30 = 0
0 + -29y = 6 + -30
-29y = 6 + -30

Combine like terms: 6 + -30 = -24
-29y = -24

Divide each side by '-29'.
y = 0.8275862069

Simplifying
y = 0.8275862069

See similar equations:

| ln(x-3)-2=8 | | 2+(-5)=x | | 2(x+4)-16=20 | | 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= | | 2+x=-(x+6) | | 2(13x-15)+3(x-19)=0 | | 2x+5+3x=15 | | h+4=-3 |

Equations solver categories